Editorial - Pacheco Romero, José (2016)
So far we have not come to understand the critical role of the microbiome in humans. It is now known that intestinal microbiota -Community of microorganisms living in the digestive tract, or flora- is a must for our homeostasis, growth, development, immunity and nutrition (1). The microbiome in man-the composition of bacteria in and on the human body-varies greatly from individual to individual, so much so that he is regarded as a 'fingerprint' for each person; this individual microbiome is associated with multiple health disorders. While microbial populations are influenced by environmental factors, there would also be some degree of host genetic influence on the microbiome, which would understand their correlation with certain diseases (2). The intestinal microbiome is being studied intensively in relation to obesity, and the involvement of factors such as diet and lifestyle in the composition of the intestinal microbiota, which could determine overweight and obesity (3) is analyzed.